2022
DOI: 10.3389/fpls.2022.805744
|View full text |Cite
|
Sign up to set email alerts
|

An Upgraded, Highly Saturated Linkage Map of Japanese Plum (Prunus salicina Lindl.), and Identification of a New Major Locus Controlling the Flavan-3-ol Composition in Fruits

Abstract: Japanese plum fruits are rich in phenolic compounds, such as anthocyanins and flavan-3-ols, whose contents vary significantly among cultivars. Catechin (C) and epicatechin (EC) are flavan-3-ol monomers described in the fruits of this species and are associated with bitterness, astringency, antioxidant capacity, and susceptibility to enzymatic mesocarp browning. In this study, we aimed to identify quantitative trait loci (QTL) associated with the content of flavan-3-ol in Japanese plum fruits. We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…GBS has become a cost-effective approach for genotyping large numbers of samples, especially the mapping populations that are required for constructing linkage maps. GBS has been employed for constructing genetic linkage maps in several fruit tree species including apple ( Oh et al., 2023 ), Japanese plum ( Battistoni et al., 2022 ), Korean pears ( Han et al., 2019 ), banana ( Sampangi-Ramaiah et al., 2023 ) and in the guava’s closest related species eucalyptus ( Zhu et al., 2023 ). In our study, GBS has been applied for the first time in SNP calling in guava mapping populations which enabled us to identify 119,343 SNPs in both parents and hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…GBS has become a cost-effective approach for genotyping large numbers of samples, especially the mapping populations that are required for constructing linkage maps. GBS has been employed for constructing genetic linkage maps in several fruit tree species including apple ( Oh et al., 2023 ), Japanese plum ( Battistoni et al., 2022 ), Korean pears ( Han et al., 2019 ), banana ( Sampangi-Ramaiah et al., 2023 ) and in the guava’s closest related species eucalyptus ( Zhu et al., 2023 ). In our study, GBS has been applied for the first time in SNP calling in guava mapping populations which enabled us to identify 119,343 SNPs in both parents and hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported here for blueberry and cranberry add to a list of works on the genetic control of flavonoid content in fruit crops, mostly in species belonging to the family Rosaceae, such as strawberry ( Labadie et al 2020 , Pott et al 2020 ), peach ( Prunus persica ; Abdelghafar et al 2020 ), Asian plum ( Prunus salicina ; Valderrama-Soto et al 2021 ; Battistoni et al 2022 ), sweet cherry ( Prunus avium ; Calle et al 2021 ), and apple ( Kumar et al 2022 ). Such studies probably have been boosted by the recent improvements in flavonoid identification and quantification methodologies and the increased interest around their beneficial health properties.…”
Section: Flavonoid Genetics In Blueberry and Cranberrymentioning
confidence: 99%